Rancang Bangun Media Pembelajaran Interaktif Mata Pelajaran Pemrograman dan Aplikasi Mikrokontroler - Umar Hamdan; Ilmiyati Rahmy Jasril (Lembaga Yasin AlSys, 2025)
Education plays a crucial role in developing students’ potential, and with the rapid advancement of information and communication technology, innovation in learning media has become increasingly relevant in creating practical, engaging, and interactive learning experiences. This study aims to design and develop interactive learning media using Adobe Animate for the subject